التحول من الادارة التسويقية إلى الرقمية دراسة تحليلية في ضوء الفكر الاداري الحديث (Al-Farooq Journal of Sciences, 2026)
This study examines the transformation from traditional marketing management to digital marketing management in light of modern administrative thought, with a focus on the Libyan context. It aims to analyze the concept of digital transformation in marketing, identify its key requirements and challenges, and highlight its role in improving marketing performance and enhancing the competitiveness of organizations.The study adopts a descriptive analytical approach, reviewing theoretical literature related to marketing management, digital marketing, and modern administrative thought. The findings indicate that digital transformation has become an essential requirement for organizations in light of rapid technological developments. However, its implementation in Libya still faces several challenges, mainly weak technological infrastructure and a shortage of qualified human resources. The study also emphasizes the importance of top management support and human resource development to ensure successful transformation.The study recommends strengthening digital infrastructure, training human resources, and promoting digital culture within Libyan institutions to improve marketing performance and achieve competitive advantage
Keywords: Digital transformation - Marketing management - Modern management thinking